Assessment of the Effects of Big Data Management on Decision-Making and Business Performance - Karagozlu, Damla; Etswaka, Jael Ntankoy; Babagil, Mustafa Tanel (Springer International Publishing Ag, 2025)
To understand the assessment of the effect of big data management on organizational performance and decision-making a scale was developed. Based on primary data from 407 big data users across different firms in Kinshasa, the capital of the Democratic Republic of the Congo, six dimensions or constructs that impact the relationship between big data management, decision-making, and company performance were proposed. The data for this investigation were analyzed using SMARTPLS software, and a survey was carried out. According to the survey, one of the most crucial areas for businesses to concentrate on ought to involve handling voluminous data since it gives a comprehensive understanding of the company, providing them with perspective, goals, and planning. The research's findings offer statistical proof of the beneficial relationship between big data management and decision-making and business performance. Indeed, a business that effectively handles big data may increase customer satisfaction, optimize marketing spending, forecast using information, save money, and lower risk.
4th International Conference on Advanced Research in Technologies Information Innovation and Sustainability-ARTIIS-Annual -- OCT 21-23, 2024 -- Universidad Andres Bello, Santiago, CHILE
Keywords: Big Data; Big Data Management; Decision-Making; Business Performance